Site-specific non-covalent interaction of the biopolymer poly(ADP-ribose) with the Werner syndrome protein regulates protein functions - Popp, Oliver (2012)
Werner syndrome is a premature aging disorder that is caused by defects in the Werner protein (WRN). WRN is a member of the RecQ helicase family and possesses helicase and exonuclease activities. It is involved in various aspects of DNA metabolism such as DNA repair, telomere maintenance, and replication. Poly(ADP-ribose) polymerase 1 (PARP1) is also involved in these processes by catalyzing the formation of the nucleic-acid-like biopolymer poly(ADP-ribose) (PAR). It was previously shown that WRN interacts with PARP1 and that WRN activity is inhibited by PARP1. Using several bioanalytical approaches, here we demonstrate that the enzymatic product of PARP1, i.e., PAR, directly interacts with WRN physically and functionally. First, WRN binds HPLC-size-fractionated short and long PAR in a non-covalent manner. Second, we identified and characterized a PAR-binding motif (PBM) within the WRN sequence and showed that several basic and hydrophobic aminoacids are of critical importance for mediating the PAR binding. Third, PAR-binding inhibits the DNA-binding, the helicase and the exonuclease activities of WRN in a concentration-dependent manner. Based on our results we propose that the transient nature of PAR produced by living cells would provide a versatile and swiftly reacting control system for WRN’s function. More generally, our work underscores the important role of non-covalent PAR-protein interactions as a regulatory mechanism of protein function.